2005
DOI: 10.1155/2005/693437
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Thiobarbituric Acid Reacting Substances and Malondialdehyde – Their Relationship to Reported Smoking and to Parodontal Status Described by the Papillary bleeding index

Abstract: Background. Thiobarbituric reacting substances (TBARS) are markers of lipoperoxidation. The best-known specific TBARS is malondialdehyde (MDA). Results from our previous studies have shown that TBARS can be measured in saliva and are increased in patients with gingivitis. Whether MDA is the main TBARS in saliva from patients with altered parodontal status is unknown. Aim. To observe the relationship between the parodontal status and TBARS, MDA and the number of epithelial cells in saliva. Subjects & Methods. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
39
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 31 publications
10
39
1
Order By: Relevance
“…Some studies was preferred examining total antioxidant activity (TAA) as a substitute of individual antioxidants in blood and other body fluids, because TAA as an incorporated parameter may provide a better marker than one antioxidant. TAA value was significantly lower than healthy controls in OLP patients which this result was agreement with several researches (Celec et al, 2005;Canakci et al, 2009;Serafini et al, 2006). ROS play important roles in immunology and inflammatory effects, and in the human body fluids, there are several antioxidants systems that have ability to maintain the stability of oxidation-reduction situation (Al-Hashimi et al, 2002;Kohen & Nayska, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Some studies was preferred examining total antioxidant activity (TAA) as a substitute of individual antioxidants in blood and other body fluids, because TAA as an incorporated parameter may provide a better marker than one antioxidant. TAA value was significantly lower than healthy controls in OLP patients which this result was agreement with several researches (Celec et al, 2005;Canakci et al, 2009;Serafini et al, 2006). ROS play important roles in immunology and inflammatory effects, and in the human body fluids, there are several antioxidants systems that have ability to maintain the stability of oxidation-reduction situation (Al-Hashimi et al, 2002;Kohen & Nayska, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…MDA is the principal and most widely studied product of polyunsaturated fatty acid peroxidation. Its interaction with DNA and proteins has often been referred to as potentially mutagenic and atherogenic 8,18,19 . Changes in the salivary antioxidant enzymes suggest that saliva may be an appropriate marker for the prognosis of oral diseases compare to the conventional invasive serum antioxidant enzyme 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the use of saliva as a diagnostic fluid have a long history. This noninvasive approach is not limited only to the diagnosis of oral diseases, because many systemic diseases, such as different types of cancers, cardiovascular diseases, immunologic syndromes, and hereditary deficiencies, can also be studied with the aid of salivary diagnostics [4][5][6][7][8] . Saliva is an accessible biofluid that contains components derived from the mucosal surfaces, gingival crevices, and tooth surfaces of the mouth.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted on diabetic rats have reported an increase in salivary and serum MDA with variable antioxidant activity (43). Celec et al (44) have found an increase in MDA levels in non diabetics which was attributed to age, altered periodontal status and smoking. Hodosy et al (45) suggest that MDA levels depend on the time of sampling and also are affected by factors like tooth brushing and antioxidative therapy received by the patients.…”
Section: Lipid Peroxidation and Protein Oxidation In Diabetesmentioning
confidence: 96%